IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KAPASITAS ASN PADA KANTOR DISTRIK MULIA KABUPATEN PUNCAK JAYA - Tabuni, Irwan; Aedah, Nur; Sapioper, Hiskia C.M. (JURNAL KEBIJAKAN PUBLIK, 2024)
This research aims to analyze and describe the implementation of the Capacity Development Policy for State Civil Apparatus at the Mulia District Office, Puncak Jaya Regency as well as the supporting and inhibiting factors for the Implementation of the Capacity Development Policy for the State Civil Apparatus at the Mulia District Office, Puncak Jaya Regency. This research is important to increase the capacity of ASN for public services and good governance in Puncak Jaya Regency. This research is qualitative descriptive research with data collection techniques used are observation, interviews and documentation techniques. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this research show that the implementation of the Capacity Development Policy for State Civil Apparatus at the Mulia District Office, Puncak Jaya Regency, Communication in its understanding is sufficient. Internal resources in developing ASN capacity are understood. The disposition in developing ASN has been carried out through efforts by the district head. Bureaucratic structure of apparatus resource management through planning, organizing, directing, controlling, procuring labor, developing, compensating, integrating, maintaining, disciplining and terminating employment relations. Apart from that, there are supporting and inhibiting factors for the implementation of the State Civil Apparatus Capacity Development Policy at the Mulia District Office, Puncak Jaya Regency based on internal factors, namely the District Head is very supportive of developing ASN capacity in accordance with applicable regulations. As well as external factors, namely environmental factors and resource factors.